Consumer Psychology of Tourism, Hospitality and Leisure. Volume 2 2001
DOI: 10.1079/9780851995359.0253
|View full text |Cite
|
Sign up to set email alerts
|

Mastering unobserved heterogeneity in tourist behaviour research.

Abstract: This paper argues that tourist behaviour research should be based on explicit hypotheses or, even better, on a system of interconnected relationships (a 'model'). The models are subject to empirical testing to assess their explanatory and predictive capabilities. As in any other sub-field of behavioural science, a sample of tourists used for model testing is often heterogeneous in terms of variable values and association between variables. Therefore, the results gained for bivariate or multivariate relations m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Marques and Reis (2015) make a valuable contribution to the tourism research discipline by stressing the importance of considering unobserved heterogeneity in PLS-SEM. Using latent class techniques, tourism researchers can assess whether or not their results are distorted by unobserved heterogeneity (e.g., Mazanec, 2000). FIMIX-PLS takes an important role in this -10 -regard as it offers a means to treat heterogeneity nonparametrically in an SEM context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marques and Reis (2015) make a valuable contribution to the tourism research discipline by stressing the importance of considering unobserved heterogeneity in PLS-SEM. Using latent class techniques, tourism researchers can assess whether or not their results are distorted by unobserved heterogeneity (e.g., Mazanec, 2000). FIMIX-PLS takes an important role in this -10 -regard as it offers a means to treat heterogeneity nonparametrically in an SEM context.…”
Section: Discussionmentioning
confidence: 99%
“…1. INTRODUCTION Accounting for heterogeneity in tourism studies remains important to avoid parameter misspecifications in empirical models (e.g., Mazanec, 2000;Mazanec, Ring, Stangl, & Teichmann, 2010). Approaches applied in tourism research that allow the examination of observed heterogeneity (e.g., Dolničar, 2004) include, for example, multi-group comparisons based on a priori information when employing regressions analysis (e.g., Ye, Zhang, & Yuen, 2013), partial least squares structural equation modeling (PLS-SEM) (e.g., Song, van der Veen, Li, & Chen, 2012), or covariance structural equation modeling (CB-SEM) (e.g., Jurowski & Gursoy, 2004).…”
Section: Guidelines For Treating Unobserved Heterogeneity In Tourism ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothesis 6 (heterogeneity): the frequency of revisiting Portugal differs by destination region and by nationalities. Barros et al (2008) have outlined that tourism choice always entails heterogeneity which should be considered when deciding what statistical models to apply (see also Mazanec, 2000). Later, Correia and Kozak (2012) demonstrated that domestic tourists have different perceptions of the regions in which they stay while in the Algarve, in the south of Portugal.…”
Section: Hypothesis 5 (Monetary Value)mentioning
confidence: 99%